Transmigrasi Dan Proses Marjinalisasi Ekonomi Orang-Orang Papua Di Tanah Papua - Rahmat Hidayat (Jurnal Mahasiswa Kreatif, 2024)
The development project through transmigration in 1984 to several islands in Indonesia, including Papua, was a neoliberal program supported directly by the World Bank. The transmigration project has opened up new consumption spaces, as well as starting the economic marginalization of the local population in Papua. The increase in the Papuan population along with the transmigration program during the New Order era was apparently unable to improve the welfare of indigenous Papuans. Transmigration in Papua succeeded in introducing new cultures or modes of economic production that replaced the old modes of production practiced by Papuans. The transmigration program in Papua has been the beginning of the economic marginalization of indigenous Papuans. The economic inequality generated by the transmigration project results in discrimination against indigenous Papuans in the field of economic endeavors. This is what happens to Papuan mothers who have to be willing to walk on sacks in front of large kiosks for immigrants in Papua. The aim of writing this article is to provide an overview of the economic marginalization created by the neoliberal development project in Papua.